Analisis Integratif Metode Hindcasting dan Pengukuran Lapangan untuk Pemodelan Tinggi dan Periode Gelombang di Pantai Glagah - David Bangguna; Irnovia Pakpahan; Marthen Tangkeallo; Henny Abulebu; Elce Bansambua; Yulisnawati Lawodi; Elizabeth Antameng; Sandi Zebua (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
The hindcasting method uses past wind data to estimate wave height (Hs) and wave period (Tp). The study aims to compare the wave height and period of the Sverdrup-Munk-Bretschneide (SMB), Finite Water Depth (FWD), and Joint North Sea Wave Project (JONSWAP) hindcasting methods with field measurement results. Wind data is sourced from NASA Prediction of Worldwide Energy Resources (POWER) Data Access Viewer (DAV) v2.4.9 for 2015-2024. The analysis results show that the wave height of the JONSWAP method is greater than the SMB and FWD methods. The wave height and period of the SMB and FWD methods have almost the same values. The difference between the three hindcasting methods is because the parameters used to calculate the wave height and period are different, the SMB method only uses the effective fetch length parameter (Feff), the FWD method uses the effective fetch parameter (Feff) and water depth (d), while the JONSWAP method uses the effective fetch parameter (Feff) and wind speed (UA). The wind speed (UA) parameter in the JONSWAP method has a very significant effect on wave height and period. For coastal structure planning, the JONSWAP method is more recommended, because the resulting wave height can function as a safety factor.